2004
DOI: 10.1523/jneurosci.1065.03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Activation of cAMP Signaling Facilitates the Morphological Maturation of Newborn Neurons in Adult Hippocampus

Abstract: Previous studies have demonstrated that activation of the cAMP cascade, including the cAMP response element-binding protein (CREB), increases the proliferation and survival of newborn neurons in adult mouse hippocampus. In the present study, we determined whether the cAMP-CREB cascade also influences the morphological maturation of newborn neurons in the subgranular zone of the hippocampus. Rolipram, a selective inhibitor of the cAMP-specific phosphodiesterase type 4, was administered to activate the cAMP casc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
131
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(148 citation statements)
references
References 52 publications
15
131
1
1
Order By: Relevance
“…This pattern could be related to the intrinsic properties of neurons or a cell type-specific contribution of Disc1 during embryonic and postnatal development dictated, at least in part, by its expression pattern (15). The mechanism behind the cellular aberrations may be related to the putative role of Disc1 at the centrosome (7) or in controlling cAMP levels (5,(27)(28)(29), although we cannot exclude other, yet-unexplored pathways. Morphological disturbances consistent with dendritic misorientation or impaired dendritic growth have been described in schizophrenia, albeit inconsistently (30,31), and a recent study provided preliminary evidence for impaired adult neurogenesis in individuals with schizophrenia (32).…”
Section: Discussionmentioning
confidence: 99%
“…This pattern could be related to the intrinsic properties of neurons or a cell type-specific contribution of Disc1 during embryonic and postnatal development dictated, at least in part, by its expression pattern (15). The mechanism behind the cellular aberrations may be related to the putative role of Disc1 at the centrosome (7) or in controlling cAMP levels (5,(27)(28)(29), although we cannot exclude other, yet-unexplored pathways. Morphological disturbances consistent with dendritic misorientation or impaired dendritic growth have been described in schizophrenia, albeit inconsistently (30,31), and a recent study provided preliminary evidence for impaired adult neurogenesis in individuals with schizophrenia (32).…”
Section: Discussionmentioning
confidence: 99%
“…These cascades are important in a variety of contexts (Antoni 2000;Jordan et al 2000) and the underlying genes are good candidates for wide-ranging pleiotropic effects. cAMP signalling has been specifically implicated in maturation of the nervous system (Fujioka et al 2004) and thus may be responsible for at least one of the observed differences between drones of the high-and low-pollen-hoarding strains.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 5 g of RNA were digested with 10 units of RNase-free DNase (Promega) for 30 min at 37°C. After DNase inactivation, RNA was retrotranscribed with an oligo(dT) [12][13][14][15][16][17][18] primer (0.5 M) and 200 units of Moloney murine leukemia virus reverse transcriptase (Invitrogen) according to the manufacturer's instructions. For real-time PCR, the following Lot1, glyceraldehyde-3-phosphate dehydrogenase, and c-fos primers were used: rat Lot, 5Ј-TTAGCTGCGTAGTTGCGTGTTA-3Ј (sense) and 5Ј-CGGGTCCCTGAAAAGAACACA-3Ј (antisense); glyceraldehyde-3-phosphate dehydrogenase, 5Ј-GAACATCATCCCTGCATCCA-3Ј (sense) and 5Ј-CCAGTGAGCTTCCCGTTCA-3Ј (antisense); and c-fos, 5Ј-TGGACCTGTCTGGTTCCTTC-3Ј (sense) and 5Ј-ATG-CACCAGCTCAGTCAGTG-3Ј (antisense).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have reported that the cAMP-PKA cascade is one of the key signal transduction pathways involved in neuronal proliferation (13,14). To define the effects of adenylate cyclase activation on CGC proliferation, we analyzed BrdUrd incorporation in cells exposed to PACAP or forskolin for 24 h after cell plating.…”
Section: Pacap and Forskolin Up-regulate Lot1 Expression Through Campmentioning
confidence: 99%
See 1 more Smart Citation